Review of the book "O Jeito que a gente diz". - Peixoto, Rafael Marcos Tort (BELT - Brazilian English Language Teaching Journal, 2015)
This is a review of the book "O Jeito que a gente diz" (2013) by author Stella O. Tagnin.